Design of differential source fed circularly polarized rectenna with embedded slots for harmonics suppression - Kumar D.; Chaudhary K. (My University, 2025)
This work presents an enhanced rectenna with a differential source feeding scheme for radio frequency (RF) energy harvesting at 2.45 GHz frequency. A circularly polarized (CP) microstrip antenna with embedded slots is designed which efficiently attains harmonics suppression. By modifying size and position of two diametrically opposite triangular projections in the top patch, two orthogonal modes that have equal magnitude and are in phase quadrature are excited. The four radial slots embedded in the antenna can block 2nd and 3rd harmonics which is suitable for onboard rectenna design without harmonics filter. A microstrip tapered feed line is used to match antenna element with 50-ohm impedance. The designed antenna is then tested for RF energy harvesting in two ways. One is conventional single source fed rectenna (SSFR), and the other is proposed differential source fed rectenna (DSFR). In the DSFR, the designed antennas are differentially operated by making a difference of λg/2 path length (λg Guided wavelength), and the ports are then connected to a differentially driven optimized rectifier circuit. For comparison, an SSFR and a DSFR are fabricated and tested. The circuit parameters in each case are optimized in Agilent Design System (ADS) 2011 software to maximize RF to direct current (DC) conversion efficiency. The proposed DSFR has a maximum efficiency (RF-DC) of 41.63% at 10dBm RF input power. In the input power range from -20dBm to 10 dBm, the DSFR has improved performance and higher efficiency over the SSFR. © 2018, Electromagnetics Academy. All rights reserved.